Christmas scarf murder [large type] - O'Connor, Carlene (Thorndike Press large print mystery series., 2022)
"CHRISTMAS SCARF MURDER by CARLENE O'CONNOR When grinchy thefts steal the good cheer at a local nursing home, Siobhan O'Sullivan manages to identify one missing item before Kilbane, Ireland's Christmas tractor parade-a hideous shamrock scarf wrapped around a very dead body. Now, with her holiday farmhouse bash approaching, Siobhan must dash to stop a deadly Secret Santa from gifting another unwanted surprise. THE UNFINISHED SCARF by MADDIE DAY It's beginning to taste a lot like Christmas at Pans 'N Pancakes, as twelve days of menu specials dazzle hungry locals. But the festivities go cold the instant a diner dies while knitting a brilliant green scarf. With Aunt Adele tied into a murder investigation, it's all on Robbie Jordan to find out who's really been naughty or nice in South Lick, Indiana. DEATH BY CHRISTMAS SCARF by PEGGY EHRHART Suspects pile up faster than New Jersey snow when frosty-tempered Carys Walnutt is found strangled by a handmade scarf auctioned at Arborville's tree-lighting ceremony. Between a winning bidder hiding behind the alias "S. Claws" and a victim who deserved coal in her stocking, can Pamela Paterson and the crafty Knit and Nibble ladies freeze a killer's merry murder plot?"--